1991
DOI: 10.1093/carcin/12.7.1181
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA adducts in HL-60 cells treated with hydroquinone and p-benzoquinone by 32P-postlabeling

Abstract: We have examined DNA adduct formation and cytotoxicity in HL-60 cells treated with either hydroquinone (HQ) or p-benzoquinone (p-BQ). Treatment of HL-60 cells with either HQ or p-BQ produced the same DNA adduct. The DNA adduct level varied from 0.05 to 10 adducts per 10(7) nucleotides as a function of treatment time and concentration for both compounds. To achieve the same DNA adduct level required higher concentrations and longer treatment times with HQ compared to p-BQ. p-BQ was also more cytotoxic to HL-60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 0 publications
4
66
2
Order By: Relevance
“…Previous studies have compared the DNA adduct formed in HL-60 cells treated with HQ with the DNA adducts formed by reaction of BQ with DNA and found that the DNA adducts formed in HL-60 cells did not correspond to the benzetheno-DNA adducts (17,34). In the present study we have found that the DNA adduct formed in vivo after benzene administration co-chromatograhed with N2-(4-hydroxyphenyl)-2'-deoxyguanosine-3'-phosphate.…”
Section: Resultscontrasting
confidence: 40%
See 2 more Smart Citations
“…Previous studies have compared the DNA adduct formed in HL-60 cells treated with HQ with the DNA adducts formed by reaction of BQ with DNA and found that the DNA adducts formed in HL-60 cells did not correspond to the benzetheno-DNA adducts (17,34). In the present study we have found that the DNA adduct formed in vivo after benzene administration co-chromatograhed with N2-(4-hydroxyphenyl)-2'-deoxyguanosine-3'-phosphate.…”
Section: Resultscontrasting
confidence: 40%
“…Following treatment, the animals were anesthetized and blood and bone marrow were collected. The levels of DNA adducts in these tissues were investigated using P1-enhanced 32P-postlabeling (17)(18)(19)27). The presence of DNA adducts was very dependent upon the benzene treatment schedule.…”
Section: Dna Adduct Formation In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, DMSO or retinoic acid induce their differentiation into polymorphonuclear cells. Recently, these myeloid cell lines have been utilized in toxicological studies (26)(27)(28). The data presented in Table 1 show that HL-60 cells have more GSH than ML-1 cells.…”
Section: Determinants Of Toxicity To Bone Marrow Cell Populationsmentioning
confidence: 99%
“…Although the metabolites responsible for this binding have not been identified (20)(21)(22)(23), our 32p_ postlabeling studies have shown that HQ and p-benzoquinone (p-BQ) form the same DNA adduct in HL-60 promyelocytic leukemia cells (24). Neither phenol nor HQ is myelotoxic by itself, but in combination they have a myelotoxic effect similar to that ofbenzene (25).…”
mentioning
confidence: 98%